PERAN DAN KONTRIBUSI PERHIMPUNAN AMATIR FOTO (PAF) BANDUNG DALAM BIDANG FOTOGRAFI INDONESIA (1954-2000) - Muhammad Rinaldy Syarifulloh; Reiza D. Dienaputra; Ayu Septiani (Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to explain the development of the Bandung Amateur Photo Association (PAF) in particular focusing on the discussion of its role and contribution in the field of Indonesian Photography in 1954-2000. The data collection method used in this research is descriptive-qualitative method with the stages through the historical method. The historical method consists of four stages, namely heuristics, criticism, interpretation, and historiography. To analyze the role and contribution of PAF Bandung in Indonesian photography, this study uses the concepts of role and contribution,. The results of this study indicate that the Bandung Amateur Photo. Association (PAF) has a role and contribution in the field of Indonesian photography, especially amateur photography. PAF has contributed to the documentation of international activities, namely the 1955 Asian-African Conference (KAA). In addition, PAF has a role in being one of the initiators of the establishment of a national photography federation, including the Indonesian Photographic Association Association (Gaperfi) and the Federation of Indonesian Photographic Associations (FPSI). PAF has always played an active role and contributed to the holding of the Indonesian Photo Salon. In addition, PAF and PAF, which is the oldest photo community in Indonesia, have succeeded in producing outstanding photographers at the national and even international levels.Keywords: PAF; Photography; Amateur Photography; FPSI; Indonesian Photo Salon.